Does CEO power affect the association between CEO compensation and tangible assets impairments? - Lee, Kin-Wai (2022)
This paper examines the association between CEO compensation and tangible long-lived assets impairment. We find that the level of CEO compensation is negatively associated with the tangible long-lived assets impairment charges. We also document that in firms with CEOs who have more decision-making power, the negative association between CEO compensation and tangible long-lived assets impairment charges is mitigated. Specifically, the negative association between CEO compensation and tangible long-lived assets impairment charges is less pronounced (1) when CEO chairs the board, (2) when CEO is the founder of the firm, (3) when the CEO is involved in the director selection process, and (4) when overall board independence is low.